A subclass of meromorphic Janowski-type multivalent q-starlike functions involving a q-differential operator - Ahmad, Bakhtiar; Mashwani, Wali Khan; Aracı, Serkan; Mustafa, Saima; Khan, Muhammad Ghaffar; Khan, Bilal; Aracı, Serkan (Springer Nature, 2022)
Keeping in view the latest trends toward quantum calculus, due to its various applications in physics and applied mathematics, we introduce a new subclass of meromorphic multivalent functions in Janowski domain with the help of the q-differential operator. Furthermore, we investigate some useful geometric and algebraic properties of these functions. We discuss sufficiency criteria, distortion bounds, coefficient estimates, radius of starlikeness, radius of convexity, inclusion property, and convex combinations via some examples and, for some particular cases of the parameters defined, show the credibility of these results. © 2022, The Author(s).
Keywords: meromorphic functions; janowski functions; q-Calculus; q-Differential operator